Duality of Large Fock Spaces in Several Complex Variables and Compact Localization Operators. (8th February 2021) - Liu, Youqi; Wang, Xiaofeng
Abstract : In this paper, dual spaces of large Fock spaces F ϕ p with 0 < p < ∞ are characterized. Also, algebraic properties and equivalent conditions for compactness of weakly localized operators are obtained on F ϕ p 0 < p < ∞ .